Deep‐intronic variants in CNGB3 cause achromatopsia by pseudoexon activation. Issue 1 (30th September 2019) - Weisschuh, Nicole; Sturm, Marc; Baumann, Britta; Audo, Isabelle; Ayuso, Carmen; Bocquet, Beatrice; Branham, Kari; Brooks, Brian P.; Catalá‐Mora, Jaume; Giorda, Roberto; Heckenlively, John R.; Hufnagel, Robert B.; et al.
Abstract: Our comprehensive cohort of 1100 unrelated achromatopsia (ACHM) patients comprises a considerable number of cases (~5%) harboring only a single pathogenic variant in the major ACHM gene CNGB3 . We sequenced the entire CNGB3 locus in 33 of these patients to find a second variant which eventually explained the patients' phenotype. Forty‐seven intronic CNGB3 variants were identified in 28 subjects after a filtering step based on frequency and the exclusion of variants found in cis with pathogenic alleles. In a second step, in silico prediction tools were used to filter out those variants with little odds of being deleterious. This left three variants that were analyzed using heterologous splicing assays. Variant c.1663–1205G>A, found in 14 subjects, and variant c.1663‐2137C>T, found in two subjects, were indeed shown to exert a splicing defect by causing pseudoexon insertion into the transcript. Subsequent screening of further unsolved CNGB3 subjects identified four additional cases harboring the c.1663–1205G>A variant which makes it the eighth most frequent CNGB3 variant in our cohort. Compound heterozygosity could be validated in ten cases. Our study demonstrates that whole gene sequencing can be a powerful approach to identify the second pathogenic allele in patients apparently harboring only one disease‐causing variant.